Tindak Pidana oleh Anak: Suatu Kajian dan Analisis Fungsi Sertifikasi Penyidik Anak di Kepolisian - Sinaga, Muhammad Ridho; Nadya Putri, Novalinda (Universitas Ekasakti, 2023)
So far, the attention to protection given to children has focused more on children who are victims or witnesses of a crime, while attention as a child of a criminal offense during the case investigation process is still relatively lacking. The fact is that not all child investigators in the police have certification as child investigators, so not all investigators understand the human rights of children that must be obtained when a child becomes a perpetrator of a crime. The research method used is the normative juridical method through a statutory approach to reviewing the legal ratio of related laws. The results of the study found that the Certification Position of child investigators is regulated based on Presidential Regulation Number 175 of 2014 concerning Integrated Education and Training for Law Enforcers. Presidential Regulation Number 175 of 2014 requires the police to participate in Integrated Training and Certification Functions for Child Investigators in the Investigation of Child Crimes by the police so that child investigators have certain knowledge and skills according to the child's condition. The expertise of special child investigators can be proven by having a child investigator certificate. Considering that UUSPA itself provides special treatment for child crimes as mandated by Article 26 of Law no. 11 of 2012, the examination and investigation of children will also be given by special investigators